PENGEMBANGAN MEDIA PEMBELAJARAN PETUALANGAN RERE BERBASIS MACROMEDIA FLASH KELAS III DI SEKOLAH DASAR - Risma Ayu Silviani; Arya Setya Nugroho (Nusantara Hasana Journal, 2022)
In the world of education, educators are required to understand and develop learning media as material to convey material to students. In addition, an educator requires innovation in the teaching and learning process. In this case, researchers take advantage of technological developments. This study aims to develop a macromedia flash-based Rere adventure learning media in class III UPT SDN 60 Gresik. This type of research is development research with the ADDIE model covering analysis, design, development, implementation, and evaluation. The subjects in this study were students of class III UPT SDN 60 Gresik as many as 23 students. Data collection techniques used media expert validation, material expert validation, and student response questionnaires. The instrument used was a material expert media expert validation sheet, and student response questionnaires. The results obtained are, 1) Macromedia flash-based learning media with an average percentage of 92.6% by media experts and material experts, can be categorized as very valid 2) Macromedia flash-based learning media with 93% student response percentage results , can be categorized as very good. Researchers hope that the use of technology in making learning media can provide a new atmosphere and the learning process will be more varied.